2017
DOI: 10.1111/ane.12734
|View full text |Cite
|
Sign up to set email alerts
|

Eslicarbazepine acetate as adjunctive therapy in clinical practice: ESLADOBA study

Abstract: ObjectiveTo assess seizure control and tolerability of eslicarbazepine acetate (ESL) as adjunctive therapy to one baseline antiepileptic drug (AED), in adults with partial‐onset seizures (POS) with or without secondary generalization.MethodsMulticenter, non‐interventional, prospective cohort study conducted between March 2012 and September 2014 at 12 neurology departments in Portugal. Adults with POS not controlled with one AED who had initiated ESL as adjunctive treatment were enrolled. Retention rate was def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…A secondary outcome measure was overall impression of response to treatment using the Clinical Global Impressions Scale (CGIS), a clinician‐determined summary measure of the patient's ability to function 10 that has been used in other epilepsy therapy trials 11 . Antiepileptic drugs (AEDs) were also documented at each time point.…”
Section: Methodsmentioning
confidence: 99%
“…A secondary outcome measure was overall impression of response to treatment using the Clinical Global Impressions Scale (CGIS), a clinician‐determined summary measure of the patient's ability to function 10 that has been used in other epilepsy therapy trials 11 . Antiepileptic drugs (AEDs) were also documented at each time point.…”
Section: Methodsmentioning
confidence: 99%
“…The Euro-Esli study was an exploratory, retrospective, pooled analysis of data from European clinical practice studies, [9][10][11][12][13][14][15][16][17][18][19][20][21] conducted to audit the effectiveness, safety, and tolerability of ESL as an adjunctive treatment for focal-onset seizures in clinical practice, details of which have been published previously. 8 In brief, effectiveness was assessed after 3, 6, and 12 months of ESL treatment and at final follow-up, and safety and tolerability were assessed for the duration of ESL treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Adverse effects (AE) reported in clinical trials were dose-dependent [16] and mainly involving central nervous (diplopia, dizziness, headache, vertigo and somnolence) and gastrointestinal system. Validation trials reported few serious ESL-related AEs and these events were generally mild to moderate, predictable, manageable and occurring during the early stages of treatment [17][18][19]. Compared to other dibenzazepines the major adverse effect appears to be hyponatremia (defined as any report of Na 135 mmol/l); during phase III studies hyponatremia was found in 18% of the patients receiving ESL, in particular on those patients with significant comorbidities and poly-therapy, versus 6% in patients receiving placebo [20].…”
Section: Discussionmentioning
confidence: 99%